Thrombocytopenia in pregnancy; prevalence, causes and fetomaternal outcome - N. Al-Husban; O. Al-Kuran; M. Khadra; K. Fram (IMR Press, 2020)
Background: Thrombocytopenia is seen in up to 12% of pregnancies. Most cases are due to benign gestational thrombocytopenia and have no adverse effects. It can, however, be due to underlying serious causes and can lead to adverse maternal and perinatal consequences. Objective: To discover the prevalence and causes of thrombocytopenia and the impact of its severity on feto-maternal outcome. Materials and Methods: This is a retrospective comparative study. Thrombocytopenia was defined as platelet count less than 150×109/L detected any time after 24 weeks gestation and averaged during prenatal visits. All thrombocytopenic pregnant patients who completed 24 weeks of gestation were included. Cases were then divided into mild (group 1, platelet count between 70 and 150×109/L) and moderate to severe (group 2, platelet count less than 70×109/L) thrombocytopenia. Results: The prevalence of thrombocytopenia in pregnant women was 7.20%. Benign gestational thrombocytopenia (BGT) accounted for 78.53%, with idiopathic (immune) thrombocytopenic purpura (ITP) accounting for 1.93%, pre-eclamptic toxaemia (PET)/HELLP syndrome accounting for 7.41%, drugs 7.23%, systemic lupus erythematosus (SLE) with or without antiphospholipid antibodies (APA) 0.84%, and various maternal diseases 4.04%. Compared with mild thrombocytopenic pregnant women (group 1), moderate to severe thrombocytopenic women (group 2) were at a significantly greater risk of caesarean section, antepartum hemorrhage (APH), postpartum hemorrhage (PPH), wound haematoma, intrauterine fetal death (IUFD), preterm delivery, and intrauterine growth restriction (IUGR). Conclusion: Thrombocytopenia is prevalent in this obstetric population with various obstetric and nonobstetric causes. The consequences of thrombocytopenia in pregnancy are mostly benign, but moderate to severe thrombocytopenia was associated with adverse obstetric and perinatal outcomes. This was due to the nature and severity of the underling maternal diseases and their medication. The authors recommend studying prospectively each of these thrombocytopenia-induced diseases in pregnancy.